2016
DOI: 10.3390/w8090380
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Runoff in the Gilgel Abbay Watershed, the Upper Blue Nile Basin, Ethiopia

Abstract: Hydrological assessment is critical to the successful implementation of adaption measures. In this study, projections of seven global circulation models (GCMs) associated with high and medium-low Representative Concentration Pathways (RCP 8.5 and RCP 4.5) for the period 2021-2040 and 2081-2100 were adopted to assess changes on runoffs in the Gilgel Abbay watershed, the upper Blue Nile basin. A weather generator was employed to generate daily temperature and precipitation to drive a hydrological model for impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
(15 reference statements)
0
23
1
Order By: Relevance
“…[39][40][41][42]. As in the Bandama watershed, the work [43] has shown that the magnitude of temperature is higher for the higher emission scenarios of RCP 8.5 than for the medium-low emission scenarios of RCP 4.5.…”
Section: Changes In Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42]. As in the Bandama watershed, the work [43] has shown that the magnitude of temperature is higher for the higher emission scenarios of RCP 8.5 than for the medium-low emission scenarios of RCP 4.5.…”
Section: Changes In Temperaturesmentioning
confidence: 99%
“…According to [45], overall projections of impacts of climate change on water resources in Sub-Saharan Africa are associated with large uncertainties. Apart from addressing the lack of observational data, key challenges for assessing climatic risks to water availability relate to their responses to heat waves, seasonal rainfall variability, as well as the relationship between land use changes, evapotranspiration, and soil moisture at different levels of global warming [43].…”
Section: Impacts Of Climate Change On Surface Watermentioning
confidence: 99%
“…Again, the shallow regolith aquifer that feeds abundant low discharge and often seasonal springs utilised by rural communities was not investigated. Moreover, abundant hydrological modelling studies exist for the Gilgel Abay catchment to better understand catchment behaviour (e.g., [27]) or more often describing likely future impacts of climate change (e.g., [28][29][30]) and of land cover change (e.g., [31][32][33]) with neither investigation nor consideration of the shallow hydrogeology with which the hydrology is inexorably connected.Our definition of shallow aquifer is an aquifer with depth of <25 m. Although there are exceptions around the world, 25 m is considered the maximum feasible depth of excavation of "hand-dug" wells [34,35]. Furthermore, much of the existing small-scale groundwater irrigation in sub-Saharan Africa depends on a water table depth of less than 5 m because of power limits on water-lifting and because of available technology; motorised pumps are much less common than manual lifting methods in the region, used in less than 20% of water-lifting cases, due to smallholder farmers' lack of capital and ability to obtain credit [2].…”
mentioning
confidence: 99%
“…Again, the shallow regolith aquifer that feeds abundant low discharge and often seasonal springs utilised by rural communities was not investigated. Moreover, abundant hydrological modelling studies exist for the Gilgel Abay catchment to better understand catchment behaviour (e.g., [27]) or more often describing likely future impacts of climate change (e.g., [28][29][30]) and of land cover change (e.g., [31][32][33]) with neither investigation nor consideration of the shallow hydrogeology with which the hydrology is inexorably connected.…”
mentioning
confidence: 99%
“…Assessment of the impact of climate change on water resources is usually performed using downscaled meteorological data from general circulation models (GCMs) due to their large grid resolution. Of the different hydrological models used to assess the impacts of climate change, Smith et al (2014) applied the Hydrologiska Byråns Vattenbalansavdelning (HBV) model to assess the impacts of climate change on flooding in the Avon catchment in the UK midlands, Gebremariam et al (2014), Kourgialas et al (2012) and Xie and Lian (2013) employed the Hydrological Simulation Program Fortran (HSPF) model for different river basins, Ayele et al (2016) applied the generalised watershed loading functions (GWLF) model to runoff in the Gilgel Abbay watershed in the upper Blue Nile basin, Ethiopia and Das et al (2013) applied the variable infiltration capacity (VIC) model to assess increased flooding in California, USA. As well as these physical-based models, different data-driven-based approaches have been presented in previous studies.…”
Section: Introductionmentioning
confidence: 99%